Real-Time E-Learning System: â€œA Tool for Students Population Decongestion in Nigeria Public Higher Institutions of Learningâ€ (A Case Study of Yaba College of Technology,Nigeria) - Ladipo, M.K.; Oyeyinka, I.K.; Yekini, N.A. (Mediterranean Journal of Social Sciences, 2012)
The focus of this research work was to develop a sustainable real-time e-learning system with the contentsto be delivered via the Internet using online real-time processing techniques. We present the conceptualframework of the model of real-time e-learning system to reduce congestion in Nigeria higher institutionsusing Yaba College of Technology as a case study. The system if developed and implemented, it willdecongest the population of students in our higher institutions, hence reduce or eliminate the problemsassociated with students population congestion in our schools.